Supplementary Figure S3 from Obesity Is Associated with Altered Tumor Metabolism in Metastatic Melanoma - Andrew W. Hahn (15024693) (2025)
Integrated gene set enrichment analysis of subgroups by body mass index BMI. This figure compares gene expression between overweight/obese (OW/OB) and normal (NL) BMI patients with metastatic melanoma across subgroups by sex, cohort, and tissue site. Supplementary Figure 2 presents a dotplot of genes differentially up- or downregulated in OW/OB patients versus NL BMI patients by subgroups. Red indicates upregulation in OW/OB verse NL.